2017
DOI: 10.1002/cad.20201
|View full text |Cite
|
Sign up to set email alerts
|

Relative Power in Sibling Relationships Across Adolescence

Abstract: During childhood, older siblings typically hold a more powerful position in their relationship with their younger siblings, but these relationships are thought to become more egalitarian during adolescence as siblings begin to prepare for their relationships as adults and as younger siblings become more socially and cognitively competent. Little is known about relationship factors that may explain this shift in power dynamics, however. The present study therefore examined longitudinal changes in adolescents' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
0
14
3
1
Order By: Relevance
“…2. At the dyadic level: studies in the field of psychology have found that as relative ability declines, the party that originally held more power will give up some power (Lindell and Campione-Barr, 2017). In other words, the shifting of capability will change the balance of inter-organizational power.…”
Section: Propositionmentioning
confidence: 99%
“…2. At the dyadic level: studies in the field of psychology have found that as relative ability declines, the party that originally held more power will give up some power (Lindell and Campione-Barr, 2017). In other words, the shifting of capability will change the balance of inter-organizational power.…”
Section: Propositionmentioning
confidence: 99%
“…Identifying moment-to-moment associations between emotion and behavior in early adolescent sibling conflict is especially critical, as sibling relationships are unique in several ways. First, unlike mother-child relationships, sibships are relatively egalitarian, especially by adolescence, when imbalances in knowledge and experience decrease (Lindell & Campione-Barr, 2017). Parent-child conflict usually ends in win-loss outcomes favoring the parent, whereas sibling conflict often results in standoffs, with children reporting high rates of passive strategies such as avoidance and withdrawal (Raffaelli, 1992; Recchia, Ross, & Vickar, 2010).…”
Section: Emotion In Family Conflictmentioning
confidence: 99%
“…Moreover, sibling relationships show dynamic changes with age. Sibling relationships transform across time from hierarchical interactions in childhood and adolescence to egalitarian exchanges by adulthood, indicating relative power changes over time (Campione-Barr, 2017;Lindell and Campione-Barr, 2017). Regarding the characteristics mentioned above, the dominant pattern of sibling interactions may vary according to specific combinations of siblings with different characters and ages.…”
Section: Sibling Relationships: As a Unique Context For Children's Dementioning
confidence: 99%
“…Sibling structural variables refer to a series of demographic factors of the sibling composition, such as sibling number, birth order, age range, and sex composition (Lindell and Campione-Barr, 2017). Many studies have been conducted to identify what sibling structural variables might affect children's ToM.…”
Section: Sibling Structural Variablesmentioning
confidence: 99%